Capital market reaction to the announcement of PSBB and PPKM policies on consumption industry companies listed on the IDX (Study on food and beverages sector companies) - Muhamad Rizky Sastra; Usep Syaipudin; Ki Agus Andi (Asian Journal of Economics and Business Management, 2022)
This article presents to find out the market's reaction to abnormal return and trading volume activity indicators to the PSBB and PPKM policies. The policy is still a hot topic of discussion among researchers, making many studies carried out since 2021. This study aims to find out and analyze the differences in Average Abnormal returns and trading volume activity on shares of consumption companies before and during the PSBB and PPKM policies. This study used a quantitative descriptive method using secondary data with a descriptive statistical test. It continued with a classical assumption test using the paired sample T-test method. Several conclusions can be drawn that there is no significant difference in abnormal returns before and during the PSBB policy and PPKM policy; there are significant differences in stock trading volumes before and during the PPKM policy. The limitation of this study is that this study uses short window periods that are unlikely to be able to capture events as a whole.